Discurso judicial e criminalização da homotransfobia no Brasil: ponderações desde uma teoria e criminologia queer - Silva, Danler Garcia (2020)
The intent of this master's thesis is to understand how the Brazilian judiciary, embodied by the Federal Supreme Court, contemplated and materialized homotransphobic violence in Brazil through the judgment of lawsuits concerning the criminalization of homotransphobia, as well as whether the criminalization of this violence is a legitimate and capable artifice to face this violence in Brazil. Through bibliographic and documentary research methods, this research is based on critical studies of criminology, sociology, anthropology and law, both in national and foreign studies, which is contemplated by books, scientific articles, as well as stricto sensu academic research and studies. Concerning documentary research, this dissertation examines a document and report on the rates of homotransphobic violence in Brazil through official data undertaken by the government, as well as examining the judgment of the Supreme Federal Court on the criminalization of homotransphobia in the country, which occurred by through the investigation of the ministers' votes concerning MI 4.733 and ADO 26. In view of this, it is based on the instrumental of critical discourse analysis to investigate the speeches instrumentalized by the ministers in their votes that deal with homotransphobic violence, sex, gender and sexuality, vulnerability, precariousness and guardianship, as well as other social markers of difference, like race, for example. Therefore, through queer theory and queer criminology, theoretical references for this research, the judicial discourse of the Supreme Federal Court that materialized homotransphobic violence, criminalizing it under the foundation of the extension and prolongation of the categories of race and racism to sexual orientation and gender identity, in a way that homotransphobia has become racism, is largely unreasonable. Furthermore, the criminalization of homotransphobia is a symbolic and derisory artifice for facing this violence, since this criminal policy understands homotransphobic violence as interpersonal violence only, ignoring the fact that this violence is structural, institutional and is immiscible in various fields of Brazilian life. Thus, since this violence in the country is real, not only understanding it, but understanding how it has been contemplated by the law and the Brazilian judiciary has become a crucial, present and meritorious object of detailing.